1997
DOI: 10.1002/(sici)1099-0917(199709/12)6:3/4<113::aid-edp151>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Heads you win, tails you lose: evidence for young infants categorizing mammals by head and facial attributes

Abstract: Four experiments were conducted with infant and adult subjects in an effort to determine the perceptual cues that are used to categorically differentiate between two common animal species, cats and dogs. The stimuli were photographic exemplars of cats, dogs and cat–dog hybrids (i.e. cat head attached to dog body and dog head attached to cat body). Experiments 1 and 2 utilized the familiarization/novelty‐preference procedure and showed that 4‐month‐old infants relied on head/face information to categorically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
7
24
1
1
Order By: Relevance
“…In sum, there was evidence for categorization of the silhouettes of cats and dogs into separate representations, even though the stimuli lacked internal facial features, which are sufficient cues for categorization (Quinn & Eimas, 1996a;Spencer et al, 1997), and the animals' typical variation in coloring. Despite this result, to conclude that categorization has occurred is premature.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In sum, there was evidence for categorization of the silhouettes of cats and dogs into separate representations, even though the stimuli lacked internal facial features, which are sufficient cues for categorization (Quinn & Eimas, 1996a;Spencer et al, 1997), and the animals' typical variation in coloring. Despite this result, to conclude that categorization has occurred is premature.…”
Section: Resultssupporting
confidence: 92%
“…The importance of the face and head region was corroborated in a study in which infants familiarized with cats or dogs preferred a hybrid animal consisting of a novel category head and familiar category body over a hybrid animal consisting of a novel category body and familiar category head (Spencer et al, 1997). Also consistent with the empirical findings indicating that the head and face region is critical for young infants' categorical differentiation of cats and dogs are simulation results from simple neural networks that failed to learn individuated representations for cats and dogs when provided with inputs reflecting only the bodily attributes (and not the head and face features) of the animal stimuli .…”
supporting
confidence: 74%
See 1 more Smart Citation
“…This characterization is consistent with the way in which the developmental literature has exploited habituation to examine infant categorization (Cohen, 2004). Developmental studies of infant categorization often habituate infants by repeatedly presenting objects from a category of stimuli, such as cats (Spencer, Quinn, Johnson, & Karmiloff-Smith, 1997) or animate objects (Legerstee, 1992), using exemplars that vary tremendously in their physical representations. In these experiments, habituation is based on the repetition of a concept or category, rather than on the perceptual attributes of the stimuli.…”
Section: A Return To Physiologymentioning
confidence: 90%
“…For example, length of trials has been found to influence infants' use of body information (Spencer, Quinn, Johnson, & Karmiloff-Smith, 1997) in categorization. We speculate that when given little time to process an object, the part of the object that most defines the category may be the part to which one first directs attention.…”
Section: Discussionmentioning
confidence: 99%